Accountants’ structured continuing professional education learning programs in Malaysia - Abd Wahab, Muhammad Syahir; Md Yusof, Mohd 'Atef (Centre for Promoting Ideas (CPI), 2013)
Continuing Professional Education (CPE) activities are paramount for accountants. Through the CPE, accountants would be able to keep abreast with current development in the profession and thus improve or at least maintain the quality of service rendered to clients. However, there is limited study on the CPE trainings for accountants. In this study, we provide insights about the CPE events organized by the Malaysian Institute of Accountants from 2006-2008. We find that financial reporting, taxation and IT trainings top the charts of training events and most trainings were done between 1-2 days (8 hours-16 hours).